The United States' Strategic Culture in Handling the Red Sea Crisis Through Operation Prosperity Guardian - Gaudialmo, Sean; Ramadhan, Jelang (Journal Research of Social Science, Economics, and Management, 2025)
A country’s foreign and defense policies are often shaped by its strategic culture, which encompasses national values, security agency principles, and historical perspectives. This study examines how the United States employed its strategic culture—characterized by a maritime vision, core national values such as equality, freedom, human rights, democracy, and liberalism—in formulating and executing Operation Prosperity Guardian to address the Red Sea crisis. The crisis, caused by the Houthi group's attacks, disrupted global trade and conflicted with U.S. values. Despite a year of operational efforts, the campaign did not yield a significant reduction in Houthi attacks, indicating limited long-term success. This qualitative research analyzes the underlying causes of this outcome by identifying four critical shortcomings within the U.S. strategic culture as applied in the operation. Through in-depth analysis, the study aims to provide a renewed understanding of how strategic culture influences policy formulation and implementation, highlighting the need for more nuanced integration of cultural factors to improve operational effectiveness. The findings offer valuable insights for policymakers seeking to enhance strategic approaches in complex conflict environments.